Viveros regionales uniformes. Vivero centroamericano de adaptacion y rendimiento VICAR 1987 - Orozco S., S.H.; Herrera C, J.M. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
The Central America Bean Yield and Adaptation Nursery (VICAR) evaluates advanced promising materials from each country over a wide range of environments. Yields of 15 red-seeded lines in 1987 are compared with those of local controls in 19 environments, and those of 15 black-seeded lines with those of a local control in 17 environments. All red lines outyielded the check Rojo de Seda; RAB 311 and RAB 310 were outstanding with yields of 1674 and 1630 kg/ha, resp. The overall yield av. for black-seeded lines was 1651 kg/ha, Tomeguin yielding highest with 2573 kg/ha. (CIAT)